The western : parables of the American dream - Wallmann, Jeffrey M., 1941- (Texas Tech University Press, 1999)
"The Western: Parables of the American Dream is the first comprehensive historical survey of the western in all of its various manifestations, from the earliest captivity narratives and pioneer biographies to contemporary western novels, films, and television series. But more, this text also contrasts the fictional and the real West. Wallmann's sweep through the western is a careful, incisive, and blessedly non-theoretical examination of the implications of the western from the beginning to the present, taking the reader deep into the heart of the subject and offering original and perceptive theories of how the western reflects the evolution of America."--Jacket.